DESAIN MODEL BASISDATA PEMELIHARAAN KOMPONEN MECHANICAL- ELECTRICAL GEDUNG SEBAGAI PENDUKUNG FACILITY MAINTENANCE MANAGEMENT (FMM) - Santosa, Stefanus; Suwarto, Suwarto; Sudarmono, Sudarmono; Setiyono, Karnawan Joko; Suwarno, Anung; Pratama, M Hafidh Aditya; Wicaksono, M Rafi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Current planning and implementation of building Mechanical-Electrical (ME) component maintenance are inefficient due to the lack of proven methods and techniques for providing accurate, non-overlapping, effective, and efficient information. Current ME component maintenance management practices and processes face numerous challenges related to data compilation and management, including data loss, wasted time searching for information, and a lack of interoperability. Research on databases, particularly in the building maintenance phase, remains limited. Data compilation is limited to scheduling and existing condition data used to generate routine maintenance reports with reference to implementation dates. This research resulted in an integrated Building MechanicalElectrical Component Maintenance Database Model to support Facility Maintenance Management (FMM). This model has met the requirements by passing the Database Reliability Test. The test used queries ranging from simple to highly complex to provide accurate, non-overlapping, effective, and efficient information needed to manage data on materials, equipment, contractors, types of work, schedules, and costs during the maintenance and repair phase.